Lactobacillus helveticus-fermented milk containing lactononadecapeptide (NIPPLTQTPVVVPPFLQPE) improves cognitive function in healthy middle-aged adults: a randomised, double-blind, placebo-controlled trial. (3rd April 2018) - Ohsawa, Kazuhito; Nakamura, Fumiya; Uchida, Naoto; Mizuno, Seiichi; Yokogoshi, Hidehiko
Abstract: This study aimed to determine the effects of a Lactobacillus helveticus -fermented milk drink containing lactononadecapeptide (NIPPLTQTPVVVPPFLQPE) on the cognitive function of healthy middle-aged adults. A randomised, double-blind controlled study was conducted in healthy participants who were randomly assigned to receive a L. helveticus -fermented milk drink (190 g/day) or the equivalent amount of a placebo drink once a day for eight weeks. Cognitive function was evaluated using the Japanese version of the repeatable battery for the assessment of neuropsychological status (RBANS) test. There was a statistically significant improvement in the total score, attention score, and delayed memory score of participants who received the L. helveticus -fermented milk drink. There was also a significant difference in the attention score between the placebo and test groups after eight weeks ( p  = .028). Therefore, supplementation of healthy middle-aged adults with a L. helveticus -fermented milk drink for eight weeks improved both attention and delayed memory.